2019
DOI: 10.1002/cpt.1565
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of EMA and FDA Decisions for New Drug Marketing Applications 2014–2016: Concordance, Discordance, and Why

Abstract: The Food and Drug Administration (FDA) and the European Medicines Agency (EMA) have robust scientific and technical collaborations. As a window to the impact of these activities we compared the agencies' decisions on drug marketing applications. Decisions were compared for 107 new drug applications with a regulatory outcome at both agencies in the period 2014-2016. Further analysis addressed individual applications for which the agencies had differing outcomes in terms of marketing approval, type of approval, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 7 publications
4
66
1
Order By: Relevance
“…Importantly, we found no further major divergences in regulatory outcomes for breast cancer drugs during the last ten years covered in our analysis (i.e., from 2009 to 2018; the two drugs approved by FDA in 2018, olaparib and talazoparib, both received an EU approval in the first half of 2019.) Our findings are in agreement with a recent analysis of new drug applications processed by the FDA and EMA between 2014-2016, which found 98% of final decisions to be concordant between the two agencies [13]. The increasing convergence of regulatory outcomes probably reflects a heightened harmonization of drug regulatory processes between the U.S.A. and Europe as well as more globally coordinated development and registration efforts by internationally active pharmaceutical companies.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Importantly, we found no further major divergences in regulatory outcomes for breast cancer drugs during the last ten years covered in our analysis (i.e., from 2009 to 2018; the two drugs approved by FDA in 2018, olaparib and talazoparib, both received an EU approval in the first half of 2019.) Our findings are in agreement with a recent analysis of new drug applications processed by the FDA and EMA between 2014-2016, which found 98% of final decisions to be concordant between the two agencies [13]. The increasing convergence of regulatory outcomes probably reflects a heightened harmonization of drug regulatory processes between the U.S.A. and Europe as well as more globally coordinated development and registration efforts by internationally active pharmaceutical companies.…”
Section: Discussionsupporting
confidence: 91%
“…Notwithstanding efforts to harmonize regulatory processes on an international level, EMA's structures and procedures diverge in various important aspects from those of the FDA. The different legal frameworks and political mandates of the two agencies can therefore result in differing regulatory timelines and/or approval decisions [12,13]. We found that 12 of the 29 breast cancer drugs in our analysis did not possess a dual approval for this tumor entity based on both the FDA and EMA review.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Our findings that the EMA approval process benefits from additional items of information only for a minority of medicines are in line with the results of a comparison of the marketing applications assessed by both the EMA and the FDA between 2014 and 2016. This study showed high concordance in the final decisions on marketing approvals (91% when only the initial decisions were considered, up to 98% including resubmission and re‐examination) . Although this study did not focus on comparisons of times to submission and approval of an application, the authors reported that the main reason for (rare) discordant decisions was differences in conclusions about efficacy, followed by differences in the clinical data submitted.…”
Section: Discussionmentioning
confidence: 85%
“…It was published recently however, that the concordance among pharmacogenomic drug labels between FDA, EMA, DPGW, and CPIC is low and of drugs considered by all agencies; for only 18% of them is the information similar across the four agencies (8). For pharmacogenomic drug labels provided by the FDA and the EMA (or the Dutch or the German MPAs), the concordance is low (8,9), in contrast to the high concordance between the FDA and the EMA regarding the approval of new drugs (10). Furthermore, the use of such labels in a clinical setting is relatively limited apart from in oncology (11).…”
Section: Introductionmentioning
confidence: 96%